مقاربات أنساق الصور السينمائية في عروض صلاح القصب المسرحية - اسعد عبد الرضا حسين ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
This research deals with the commonalities between theater and cinema technicians, the extent to which these two techniques are close to each other, the mutual influence between them, and attempts to indicate the points of participation for the reasons for these two arts and Iraqi theatrical performances that adopted in their activities this type of work and the extent of the success of this marriage in conveying dimensions The intellectual and aesthetic framework of the theatrical presentation, as the research included two chapters of the first chapter of two researches. The first was the curricular framework and the second research was a theoretical framework. Thesecond chapter was the research procedures from an analysis of samples after which the results, conclusions and recommendations and finally a list of sources